The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcvm.2021.750965
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Limits of Ejection Fraction and Ventricular-Arterial Coupling in Heart Failure

Abstract: Left ventricular ejection fraction (LVEF) and ventricular-arterial coupling (VAC) [VAC = Ea/Ees; Ea: effective arterial elastance; Ees: left ventricle (LV) elastance] are both dimensionless ratios with important limitations, especially in heart failure setting. The LVEF to VAC relationship is a divergent non-linear function, having a point of intersection at the specific value of 0.62, where V0 = 0 ml (V0: the theoretical extrapolated value of the volume-axis intercept at end-systolic pressure 0 mmHg). For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
7
0
2
Order By: Relevance
“…Naturally, E V is linked with the LV ejection fraction (LVEF). In a study underlying the limits of LVEF in heart failure, E V was found to be strongly correlated with different times of the cardiac cycle ( 10 )—a relation that was also suggested by other studies ( 11 , 12 ). This finding opens an interesting research niche regarding the relation between ventriculo-arterial coupling and electromechanical coupling—a subject that has never been studied in critically ill patients.…”
Section: Introductionsupporting
confidence: 66%
“…Naturally, E V is linked with the LV ejection fraction (LVEF). In a study underlying the limits of LVEF in heart failure, E V was found to be strongly correlated with different times of the cardiac cycle ( 10 )—a relation that was also suggested by other studies ( 11 , 12 ). This finding opens an interesting research niche regarding the relation between ventriculo-arterial coupling and electromechanical coupling—a subject that has never been studied in critically ill patients.…”
Section: Introductionsupporting
confidence: 66%
“…This fact is nicely illustrated in Table 2 of the Zand et al paper, with similar EF for super‐responders and the comparison group, while yet both ESV and EDV differ significantly 3 . Elsewhere it is explained how limitations concerning EF and other dimensionless metrics can be compensated by the introduction of an obvious companion metric 7,8 …”
Section: Ef or Esv As Criterion To Predict Super‐respondersmentioning
confidence: 72%
“…However, in an in vivo setting, vascular, humoral, and neuronal factors must also be considered in conjunction with cardiac function [ 54 , 55 ]. Since the ejection fraction is calculated based on ventricular volumes, dilation of the ventricle may skew this index without any significant change in contractility [ 56 ]. Hence, the reduced ejection fraction may reflect either an elevated afterload, the dilation of the ventricles previously described for α 2 +/G301R mice, or a combination of the two [ 26 , 27 , 47 ].…”
Section: Discussionmentioning
confidence: 99%